Enhancing Confidence and Reducing Anxiety: Zoom Meetings in EFL Speaking Practice - Raden Hasby Isnaindy Fasa; Fazri Nur Yusuf; Pupung Purnawarman; Noraini Binti Said (Pedagogy Review, 2026)
Speaking anxiety represents one of the most persistent barriers to oral language development among EFL learners in higher education, yet the specific mechanisms through which technology-mediated presentation environments address this challenge remain insufficiently understood. This study explores EFL students' experiences and perceptions of Zoom Meeting-based presentations, with particular attention to how specific platform features help reduce speaking anxiety and enhance speaking confidence in an Indonesian university context. A qualitative case study design was employed, involving six purposively selected undergraduate EFL students enrolled in an advanced English-speaking program at a university language center in Indonesia. Data were collected over six weeks through three complementary sources: classroom observations, semi-structured individual interviews lasting 15 to 20 minutes, and document analysis of presentation slides, instructor feedback, and participant self-reflection essays. Data analysis followed Braun and Clarke's (2006) six-stage thematic analysis framework. Four principal themes emerged from the analysis. First, Zoom's camera control and hidden notes features were perceived as meaningful anxiety-reducing affordances, enabling students to redirect cognitive attention from self-presentation concerns toward linguistic performance. Second, private rehearsal capabilities significantly enhanced students' sense of preparedness before formal presentations. Third, interface customization options supported improved focus and a sense of environmental control during delivery. Fourth, participants identified notable constraints, including technical difficulties, audio latency, and reduced authentic communicative interaction due to limited nonverbal feedback. The findings suggest that Zoom's platform-specific affordances may support confidence development and anxiety management in EFL presentation contexts, particularly for learners with heightened speaking anxiety. However, these benefits appear to be contingent on deliberate pedagogical design that treats the platform's supportive features as temporary scaffolds rather than permanent accommodations and progressively reintroduces authentic communicative demands as learners' confidence grows. Keywords: Online presentation, Technology-mediated language learning, Speaking anxiety, Zoom meeting